Athlete perceptions of social media benefits and challenges during major sport events - Michelle Hayes; Kevin Filo; Caroline Riot; Andrea Geurin (2019)
Numerous studies have focused on athletes’ use of social media by examining the content posted on social media sites, revealing an opportunity to gather firsthand experiences from athletes. Using uses-and-gratifications theory as a theoretical framework to inform an open-ended questionnaire, the authors examined athlete attitudes toward their social media use during a major sport event, as well as the gratifications they received and the challenges they experienced from this use. The study assessed a sample of 57 athletes and their social media use across 20 international major sport events. Findings revealed that social media enabled athletes to communicate with family and friends. Having a connection to home through social media can make athletes feel relaxed in a high-pressure environment. The results reveal uses and gratifications not previously found in research on athlete social media, while also underscoring opportunities for sport organizations to enhance social-media-education programs they provide to athletes.